2018
DOI: 10.1002/jlb.mr0318-120r
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal HIV exposure, feeding status, and microbiome on infant cellular immunity

Abstract: At least one-third of infants born in sub-Saharan Africa have been exposed to the effects of maternal HIV infection and antiretroviral treatment. Intrauterine HIV exposure is associated with increased rates of morbidity and mortality in children. Although the mechanisms responsible for poor infant health with HIV-1 exposure are likely to be multifactorial, we posit that the maternal environment during gestation and in the perinatal period results in altered infant immunity and is possibly the strongest contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…Indeed, HEU infants display high morbidity and mortality from pneumonia, diarrheal disease and sepsis [13,14] as well as poor growth and neurodevelopment [15]. The underlying reasons for such clinical differences are most likely multifactorial and dependent on the geographical and social setting, maternal health status and breastfeeding [16][17][18][19]. Of note, recent data have demonstrated that maternal HIV infection is linked to modifications in the fecal microbiome of HEU with alterations in the abundance of several taxa and functional profiles, suggesting that gut dysbiosis may contribute to the clinical vulnerability in this setting [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, HEU infants display high morbidity and mortality from pneumonia, diarrheal disease and sepsis [13,14] as well as poor growth and neurodevelopment [15]. The underlying reasons for such clinical differences are most likely multifactorial and dependent on the geographical and social setting, maternal health status and breastfeeding [16][17][18][19]. Of note, recent data have demonstrated that maternal HIV infection is linked to modifications in the fecal microbiome of HEU with alterations in the abundance of several taxa and functional profiles, suggesting that gut dysbiosis may contribute to the clinical vulnerability in this setting [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This issue of JLB features a number of manuscripts describing these infectious diseases, including data on the impact of maternal HIV‐exposure, feeding status, and the microbiome on infant cellular immunity, as reported by Clive Gray and colleages . The pathogenesis of tuberculous meningitis is described by Robert Wilkinson and Benabdessalem and their colleagues and shows how granzyme B induced by Rv0140 antigen in latently infected individuals with tuberculosis is different from those with active tuberculosis.…”
Section: Research Presented During the 10th Federation Of African Immmentioning
confidence: 99%
“…The same is true for genotypes and haplotypes whose repertoire varies from one individual to another and within different populations (Toneva et al 2001; Yawata et al 2002). Several studies have shown that exposure to antiretroviral therapy and HIV is a determinant of high mortality, morbidity and susceptibility to diseases in HEU compared to HUU (A. L. Slogrove et al 2016; Brennan et al 2016; Abu-Raya et al 2016; Ruck et al 2016; Desmonde et al 2016; Dzanibe et al 2019; Gabriel et al 2019). In addition, social, parental and domestic conditions, the role of poverty, maternal and environmental risk factors have been identified by several recent reviews as explanatory factors for high mortality and morbidity among HEU children (A.…”
Section: Introductionmentioning
confidence: 99%